Effectiveness and safety of the bevacizumab and erlotinib combination versus erlotinib alone in EGFR mutant metastatic non-small-cell lung cancer: systematic review and meta-analysis - Motta-Guerrero, Rodrigo; Leon Garrido-Lecca, Alejandro; Failoc-Rojas, Virgilio E.; Calle-Villavicencio, Ana; Villacorta-Carranza, Robert; Huerta-Collado, Yesenia; Torres-Mera, Alicia; Valladares-Garrido, Mario J.; Rivera-Francia, Víctor; Carracedo, Carlos; Raez, Luis (Frontiers in Oncology, 2024)
The EGFR gene encodes a protein that stimulates molecular pathways that allow the growth and development of the tumor microenvironment. The current preferred TKI for first-line treatment of EGFRm metastatic NSCLC is osimertinib. However, the combination of angiogenesis inhibitors and TKI has produced discordant results. We aimed to assess the effects of the Bevacizumab and Erlotinib combination in EGFRm metastatic NSCLC. Methods: Using eligibility criteria focused on patients with EGFRm metastatic NSCLC treated with Bevacizumab and Erlotinib, we searched databases including clinical trial randomized studies, and reviews published until April 15, 2023, in Medline (PubMed), Scopus, and Embase. Eight clinical trials (1052 patients) were selected from 1343 articles for quantitative and qualitative assessment. The risk of bias was assessed using the Cochrane Risk of Bias tool. Data were synthesized through random-effects meta-analysis. Results: The Bevacizumab and Erlotinib combination significantly improved PFS (Log (HR)=0.63; 95% CI: 0.54-0.73, p<0.001) and ORR (RR = 0.79, 95% CI; 0.64-0.97, p=0.03). However, it did not improve OS (Log (HR) = 0.93; 95% CI; 0.78-1.10, p = 0.38) and was associated with higher SAEs (OR = 3.48, 95% CI; 1.76-6.88, p=0.005). Subgroup analysis suggested similar benefits in different mutation subtypes and brain metastasis condition. The evidence is limited by a moderate risk of bias across studies and heterogeneity in the reporting of SAEs. Conclusions: The Bevacizumab and Erlotinib combination significantly improved PFS and ORR in EGFRm metastatic NSCLC but were also associated with higher grade ≥3 adverse events. These results suggest that while the combination therapy may enhance progression-free survival and overall response, it does not improve overall survival and is associated with higher toxicity. Thus, the treatment should be personalized based on individual patient comorbidities. Further prospective trials are needed to validate these results.